Implementasi Pendekatan Myers-Briggs Type Indicator Dalam Sistem Informasi Bimbingan Konseling Berbasis Android Untuk Sekolah Menengah Atas - Andi Mulawati Mas Pratama; Misrawati Aprilyana Puspa; Herlianti Nusi (JSAI (Journal Scientific and Applied Informatics), 2025)
Guidance and counseling services at SMA Negeri 3 Gorontalo Utara play a crucial role in helping students recognize their potential, interests, and the problems they face. This study aims to develop an Android-based guidance and counseling information system by integrating the Myers-Briggs Type Indicator (MBTI) approach as a tool for identifying students' personality types. The system is designed to present the MBTI questionnaire, automatically analyze the results, and provide counseling recommendations that correspond to each student's personality type. Testing was conducted on 60 eleventh-grade students at SMA Negeri 3 Gorontalo Utara. The results show that the system is capable of effectively classifying personality types and delivering relevant recommendations. The most commonly found personality types were INFP, ESTJ, and ISFJ. Both students and guidance counselors responded positively to the system's usability, ease of use, and clarity. Although limitations remain in terms of advanced personalization and data integration, the approach has proven to enhance the quality of counseling services in a more adaptive and technology-based manner. This study recommends further feature development and system integration into the school's academic management